Coronary Artery Ectasia Presenting as a Non-ST Elevation Myocardial Infarction in a Young Adult: Case Presentation and Literature Review - Kareem Genena; Mir Ali; Donald Christmas; Henry Siu (Case Reports in Cardiology)
While acute coronary syndromes most commonly occur secondary to unstable atherosclerotic plaque, coronary aneurysms, also known as coronary artery ectasia (CAE), represent a less common etiology. Whereas coronary atherosclerosis accounts for about 50% of CAE, the remaining 50% are either congenital or secondary to a host of inflammatory and connective tissue disorders, with Kawasaki disease being a well-known association. Patients with CAE have worse outcomes than the general population regardless of the presence of associated atherosclerotic coronary artery disease. We report the case of a young male presenting with chest pain, a right bundle branch block on electrocardiography, an elevated troponin level, and a regional wall motion abnormality on echocardiography who is found to have diffuse coronary artery ectasia on coronary angiography and is managed medically with dual antiplatelet therapy.